Evelina Fernández’s Mexican Trilogy: ‘Setting the Record Straight’ - Rizk, Beatriz J. (Latin American Theatre Review, 2018)
In this article I review Evelina Fernández’s trilogy of plays, Hope, Faith, and Charity. The trio tells a semi-autobiographical family saga covering nearly one hundred years. Throughout the plays, Fernández addresses big issues in everyday life, using national and international arenas of international politics as a background. Passing through the Mexican Revolution, the Great Depression, WW II, the Cuban Missile Crisis, and the War in Iraq, the Mexican Trilogy gauges the effect these events have in the lives of the women in Fernández’s family, underlining the social practices in which various inequalities (gender, racial, and ethnic) are played out. Crossing the boundaries and thinking creatively about her family migration experience, Fernández shows us new ways of understanding social relations in pursuit of “setting the record straight” on behalf of the strong women who preceded her.